In Silico Discovery of Potent LpxC-Binding Compounds from Paederia foetida (Daun Kentut) as Promising Candidates against Gram-Negative Bacterial Infections - Lisa Savitri; Kharisul Ihsan; Elfred Rinaldo Kasimo; Rochmad Krissanjaya (Biology, Medicine, & Natural Product Chemistry, 2026)
The increasing prevalence of multidrug-resistant Gram-negative bacteria necessitates the discovery of novel antibacterial agents targeting essential bacterial enzymes. Lipopolysaccharide biosynthesis enzyme LpxC represents a promising target due to its critical role in maintaining bacterial outer membrane integrity and its absence in mammalian cells. This study aimed to identify potential LpxC inhibitors derived from Paederia foetida (Daun Kentut) using an integrated in silico approach. Bioactive compounds reported from P. foetida were subjected to molecular docking against LpxC, followed by protein–ligand interaction analysis, molecular dynamics simulations, binding free energy calculations, and ADMET prediction. Docking results revealed that several compounds exhibited strong binding affinity toward the LpxC active site, with PF-01 showing the most favorable binding energy (-9.2 kcal/mol) and stable zinc coordination. Molecular dynamics simulations confirmed the structural stability of the PF-01–LpxC complex, as indicated by low RMSD and RMSF values throughout 100 ns simulation. MM/PBSA analysis demonstrated that van der Waals and electrostatic interactions were the dominant contributors to binding stability. ADMET prediction suggested that while PF-01 showed slightly limited drug-likeness due to molecular size, it remained non-toxic and pharmacologically acceptable. Overall, this study provides molecular-level evidence supporting P.foetida as a promising natural source of LpxC-targeting compounds and proposes PF-01 as a potential lead candidate for further experimental validation against Gram-negative bacterial infections.